Advanced monitoring techniques of a company’s social capital - Kulibanova Valeriia (Peter the Great St. Petersburg Polytechnic University, 2021)
For the company, the accumulated social capital provides a reliable support for long-term trusting relationships with all stakeholder groups contributing to its stability in crises. It is at the present stage the property of social capital to help withstand various kinds of challenges seems particularly relevant. A higher educational institution in this context is not an exception. Like any other organization, a university is able to convert social capital into real economic advantage and benefit from the developed social connections. The higher education system is one of the most important areas affected by the general digitalization. In the current context, the competitiveness of any educational institution and ultimately its survival in the new information environment depend on how timely a university engages in this process. The unprecedented changes brought about by digitalization have been amplified by the COVID-19 pandemic, which has had a significant impact on social connections, transforming norms of reciprocity and trust, social relations and principles of social interaction. In the context of increasingly severe competition, social capital can become the most important intangible asset for a university, being a reliable support to form long-term trusting relationships with all stakeholder groups. It is the accumulated social capital that will enable higher education institutions to effectively withstand new challenges. It should be emphasized that any university’s social capital is closely associated with the information found both in the offline space and in the virtual environment. That is why the monitoring of social capital should take into account both real communications and the “digital footprint”, which forms the media image of the university and directly affects the improvement of its competitiveness. The purpose of this study is to develop modern methods of monitoring the organization’s accumulated social capital in the online environment. The authors considered the main directions of social capital accumulation for higher educational institutions. The monitoring criteria and measuring procedures of university’s social capital under interaction with different groups of stakeholders were defined. A comparative analysis of social capital of leading universities in St. Petersburg was carried out for the two most important groups, namely consumer and diffuse groups. The results of the study can be used by universities to monitor the social capital in the formation of communication strategies with different stakeholder groups in order to maximize the effectiveness of these procedures.